Advancements in Passwordless Authentication: The Future of SSO in Cloud IAM (Cybersecurity and Network Defense Research, 2023)
The evolution of passwordless authentication in cloud-based identity and access management system shows the paradigm shift in enterprise security. Traditional password-based authentication systems are becoming vulnerable to phishing attacks, credential thefts, brute force attacks, these attacks results in adaptation of advanced authentication models. The aim of this paper is to explore contemporary password less authentication technologies such as biometric authentication, hardware security keys, and cryptographic techniques like WebAuthn and FIDO2.